Predictive power of the term structure of interest rates over recessions in Europe - Pinho, Carlos (2017)
This work intends to infer for European countries the extent that anticipations of the term structure of interest rates has over recessions, as measured by factor models. For that, we model the shape of the yield curve by latent factors corresponding to its level, slope and curvature. The simple and modified probit and logit models are used to examine the yield curve’s ability to forecast economic downturns (recessions). Despite official recessions dates being available at the Centre for Economic Policy Research (CEPR), which recently formed a committee to set the dates of the Euro area business cycle in a manner similar to the NBER, these are based on aggregate data. So, we determine the recessions using the BBQ methodology to have them dated for each individual country in the sample. The findings suggest that the yield curve components predict recessions for more than one year ahead, with increased goodness of fit when the autoregressive term is included as explanatory variable. These results are consistent for both UK, Germany and Portugal.